Development and Performance Validation of a Falling Weight Impact Tester for Coating Resistance Evaluation - Imah Luluk Kusminah; M. ‘Abid Muzayyin; M. Karim Alamin (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
This study presents the design, fabrication, and performance evaluation of a falling-weight impact testing apparatus for assessing the impact resistance of protective coatings in accordance with ASTM D2794-93: Standard Test Method for Resistance of Organic Coatings to the Effects of Rapid Deformation (Impact). The developed apparatus was designed to overcome limitations reported in previous studies, particularly regarding measurement accuracy, structural stability, and testing repeatability. The testing system was employed to evaluate the impact resistance of coated flat metallic specimens with a coating thickness of 900 ± 100 µm under controlled impact loading conditions. The experimental investigation examined the influence of two impact masses (1.8 kg and 3.6 kg) and three drop heights (0.50, 0.70, and 0.90 m), corresponding to different impact energy levels, on coating performance. The coating response was assessed by analyzing the occurrence and propagation of coating defects, particularly crack initiation after impact loading. The results demonstrate that the developed apparatus provides stable and consistent testing conditions while complying with the dimensional and operational requirements specified in ASTM D2794-93. Furthermore, variations in impact mass and drop height significantly influence the severity of coating damage, indicating that applied impact energy plays a critical role in determining coating resistance. The developed testing apparatus offers a reliable, accurate, and cost-effective alternative for laboratory-scale impact testing of protective coatings on metallic substrates and can support future research on coating performance evaluation and quality assurance. Contribution to Sustainable Development Goals (SDGs):SDG 8: Decent Work and Economic GrowthSDG 9: Industry, Innovation and InfrastructureSDG 11: Sustainable Cities and Communities